Perceptions of females about trauma-informed services for survivors of sexual violence in south western Uganda- a qualitative study - Earnest Amwiine; Bonita Ainembabazi; Isaiah Obwona; Richard Opoka; Mary Akatuhumuriza; Vallence Niyonzima; Vincent Mubangizi (BMC, 2021)
Abstract Background Sexual violence is a public health concern globally and locally, and trauma-informed services are put in place to mitigate its consequences. A few studies have evaluated the quality and uptake of these trauma-informed services for sexual violence. This study aimed at; i) assessing the knowledge of participants about trauma-informed services, ii) exploring the attitudes of females about trauma-informed services, and iii) assessing different factors associated with the utilization of trauma-informed services. Methods This study employed a descriptive cross-sectional qualitative design. The participants were females at Kyangyenyi health center III and Kigarama health center III in Sheema district, southwestern Uganda. We used a purposive sampling procedure for all participants and then a consecutive sampling of females. Data about; knowledge of trauma-informed services for sexual violence, attitudes towards trauma-informed services, and factors influencing the utilization of trauma-informed services were collected using an in-depth interview guide. Data were analyzed using thematic content analysis. Results We interviewed 32 participants. There was a high prevalence of sexual violence, and it was a big concern in the community. Many of the respondents were not sensitized about trauma-informed services. Most of them knew only about HIV treatment. Our study shows that a good section of females did not seek the services after being sexually violated due to the fear of the perpetrator, bribing of the family of the affected and authorities, or even fear of family breakup and stigmatization. There were a lot of bribery, poor road networks, and inadequate health care services. These hindered survivors of sexual violence from utilizing trauma-informed services. Conclusions There was a knowledge gap about trauma-informed services for survivors of sexual violence. There was sexual violence in the community. Sensitization needs to be done among the populations by respective authorities to iron out issues of ignorance about the services and health workers evaluated for competence in offering the trauma-informed services.